Identyczności (przyczynek do słownika filozoficznego) - Tędziagolska, Joanna (Filozofia Nauki, 1995)
The principal aim of this paper is to analyse the notion of identity and to clarify terminology relevant to this notion. I characterize two main types of identity occuring between objects: abstract identity and numerical identity. I introduce further subtypes and try to point out some of the relations between objects which are identical numerically, and those which are identical abstractly. Some of the qualities of identity are described. Then, I work over relationship between identity and the other relations: sameness, kinship, likeness, equivalence, equality and difference. I also point out some of consequences of the view which reduces synonimity of expression to identity between these expressions' meanings. Finally, I consider the criterion which would make identification of identity possible.